Substance use and other correlates of HIV infection among transwomen and men who have sex with men in Perú: Implications for targeted HIV prevention strategies for transwomen. - Elena Cyrus; Javier R Lama; Jorge Sanchez; Daniell S Sullivan; Segundo Leon; Manuel V Villaran; Panagiotis Vagenas; David Vu; Makella Coudray; Frederick L Altice (Public Library of Science (PLoS), 2023)
Characterization of HIV risk factors among transwomen and men who have sex with men (MSM) should be assessed separately and independently. However, due to several constraints, these populations continue to be conflated in clinical research and data. There are limited datasets globally powered to make such comparisons. The study aimed to use one of the largest surveys of transwomen and MSM in Latin America to determine differences in HIV risk and related correlates between the two populations. Secondary data analysis was completed using a cross-sectional biobehavioral survey of 4413 MSM and 714 transwomen living in Perú. Chi Square analysis of selected HIV correlates was conducted to examine differences between transwomen and MSM. Additionally, stratified binary logistic regression was used to split data for further comparative analyses of correlates associated with transwomen and MSM separately. HIV prevalence among transwomen was two-fold greater than among MSM (14.9% vs. 7.0%, p<0.001). Transwomen had a higher prevalence of most HIV risk factors assessed, including presence of alcohol dependence (16.4% vs. 19.0%; p < .001) and drug use in the past 3 months (17.0% vs. 14.9%). MSM were more likely to use marijuana (68.0% vs. 50.0%, p < .001), and transwomen were more likely to engage in inhaled cocaine use (70.0% vs. 51.1%, p < .001). The regression exposed differences in correlates driving sub-epidemics in transwomen vs. MSM, with a trend of substance use increasing HIV risk for transwomen only. Transwomen were more likely to be HIV-infected and had different risk factors from MSM. Targeted prevention strategies are needed for transwomen that are at highest risk. Additionally, further research is needed to determine if these observations in Perú regarding substance use patterns and the role of substance use in HIV risk relate to other trans populations globally.